Responding to climate related risks to address food insecurity in Nyando, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Since 2011, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) is facilitating a partnership around collective action in seven villages that integrates a science approach to deliver development outcomes in Nyando. The approach is based on a climate-smart village (CSV) model, focusing on improving local knowledge of climate risks and variability in seasonal rainfall, dry spells, and diseases and pests to inform farming decisions. The goal is to respond to climate variability, improve food security and enhance household incomes. This is achieved through the participatory testing of resilient technologies, training to build the knowledge and capacity to change local practices and improve planning for adaptation to changing farming conditions. Through participatory action research approaches, the partnership is facilitating the testing of a portfolio of climate-smart agriculture (CSA) interventions, allowing farming households to make progressive changes to their crops and cropping patterns as well as introducing new resilient livestock breeds. The new livestock breeds are able to withstand heat stress, better utilize low quality forage, cope with the disease burden, recover from drought with faster compensatory growth, therefore maturing to market weight within a shorter period compared to the local breeds. The farming households are able to combine these scientific tools and products with changes from adaptive management to address climate related risks and build resilience at local scales.